Early acupuncture intervention strongly associates with improved swallowing recovery in post-stroke dysphagia: a multicenter real-world cohort study - Li, Junlong; Li, Guiping; Wang, Shu; Li, Li; Wang, Fei; Yang, Chen; Shen, Yan; Yang, Sha; Xu, Zhijie; Xu, Fan; Lu, Mengnan; Wang, Xiaomei; et al. (Frontiers in Neurology, 2025)
BackgroundPost-Stroke Dysphagia (PSD) is a common complication of stroke, significantly impairing recovery and quality of life. Acupuncture has shown potential in improving swallowing function, yet the optimal timing of intervention remains unclear. This study evaluated the effect of acupuncture timing on swallowing recovery in stroke patients.MethodsWe conducted a multicenter real-world study across 27 hospitals in China, enrolling 382 stroke patients with PSD. Inclusion required symptom onset within 90 days and a Water Swallowing Test (WST) score > 2. The primary outcome was swallowing function recovery at discharge, 90 ± 7 days, and 180 ± 7 days post-onset. Multivariate logistic regression was used to adjust for potential confounders.ResultsAmong 359 participants with complete data, early acupuncture (0–14 days post-stroke) was strongly associated with improved swallowing recovery. Delayed treatment beyond 28 days significantly reduced recovery odds at discharge (adjusted OR = 2.17; 95% CI: 1.12–4.21) and 90 days (adjusted OR = 2.57; 95% CI: 1.31–5.04). This effect diminished at 180 days (adjusted OR = 1.55; 95% CI: 0.52–4.61). Medullary lesions and diabetes were also associated with poorer outcomes, while hyperlipidemia showed a potential protective effect. The study relied on WST as the sole functional assessment, which, while practical, lacks the sensitivity of instrumental measures like VFSS or FEES for detecting silent aspiration.ConclusionEarly acupuncture intervention within 2 weeks post-stroke is strongly associated with improved swallowing recovery in real-world clinical practice. Delayed treatment may limit clinical benefit. Future research should incorporate instrumental swallowing assessments and randomized trials to refine acupuncture timing and validate these findings.Clinical trial registrationChiCTR2100042721.